Effect of Tillage and Herbicides on Weeds and Yield of Maize (Zea mays L.) - Choudhary, Dinesh; Chhokar, Rajender Singh; Gill, Subhash Chander; Samota, Shiv Ram; Kumar, Nitesh; Yadav, Girdhari Lal (Journal of Cereal Research, 2022)
Based on this study, it can be concluded that for achieving effective weed control, and higher maize yield and profitability, combinations of conservation tillage (zero tillage + 6 t ha-1 residue) with tank mixture of either atrazine + tembotrione + halosulfuron at 800+90+67.5 g ha-1 or atrazine + tembotrione + bentazone at 900 + 90 + 960 g ha-1 as post-emergence can be adopted.